Investigating the effects of g-C3N4/Graphene oxide nanohybrids on corrosion resistance of waterborne epoxy coatings. (October 2021) - Zhou, Ziyang; Ji, Xiaohong; Pourhashem, Sepideh; Duan, Jizhou; Hou, Baorong
Highlights: 2D nanohybrids of graphene oxide and g-C3 N4 (GO@CN) are synthesized. GO@CN nanohybrids are chemically functionalized with silane (F-GO@CN). Waterborne epoxy coatings loaded with 0.1 wt% F-GO@CN nanohybrids are prepared. Nanocomposite coatings show superior corrosion resistance in NaCl solution. Nanocomposite coatings have higher adhesion strength and less hydrophilicity. Abstract: Two dimensional nanomaterials including graphene oxide (GO), graphitic carbon nitride (CN), and their nanohybrids (GO@CN) are used for enhancing the corrosion resistance of waterborne epoxy coatings. The nanomaterials functionalized with 3-aminopropyltriethoxysilane are loaded in the waterborne epoxy matrix by solution mixing method through probe-sonication and mechanical mixing. The corrosion resistance of the pure waterborne epoxy (PE) and the nanocomposite coatings in 3.5 wt% NaCl solution is evaluated by electrochemical impedance spectroscopy and salt spray test; revealing that the epoxy coating loaded with 0.1 wt% silane functionalized GO@CN nanohybrid has the highest chemical stability and corrosion resistance, due to the well-distribution of the nanohybrid in the polymer matrix. This research exhibits the importance of developing nanocomposite coatings based on two dimensional nanohybrids to overcome the shortcomings of the nanomaterials and to simultaneously utilize from their advantages in a coating system.